PRODUKTIVITAS ANGKUTAN LORI DORONG DI HUTAN JATI - Apul Sianturi (Jurnal Penelitian Hasil Hutan, 1984)
A study on the productivity of lorry transportation in the teak forest was carried out in 1982, at  three forest  Districts. Time study have been conducted for this purpose.The Study shows that:Log loading productivity of a 6-men crew are 2.2, 1.7, and 1 m3 per hour in the Bojonegoro Mantingan, and Blora Forest Districts respectively with an average of 1.6 m3 per hour.Loading capacity of one lorry varies from 2. 6 to 4.7 m3 of logs with an average of  3.6 m3.Lorry speed varies from 5.7 to 8.6 km per hour, with an average of 6.9 km per hour.Unloading productivity varies from 5.6 to12.9 m3 per hour, with an average of 7.5 m3 per hour.Hauling cost varies from Rp. 86 to Rp. 92 per m3km, with an average of Rp. 88 per m3 km.